THE RELATION OF CARDIOVASCULAR HEALTH WITH PROFESSIONAL OCCUPATION (ESSE-RF IN KEMEROVO REGION) - S. A. Maksimov; T. A. Mulerova; E. V. Indukaeva; Ya. V. Danilchenko; M. V. Tabakaev; N. V. Cherkass; G. V. Artamonova (Кардиоваскулярная терапия и профилактика, 2015)
Aim. Analysis of the prevalence of cardiovascular diseases and risk factors depending on occupation.Material and methods. Under the multicenter epidemiological study ESSE-RF (Epidemiology of Cardiovascular Diseases and their Risk Factors in Russian Federation) the questioning performed and 1627 persons investigated in Kemerovo Region at the age 25-64 y.o. Two comparison groups were created: employed (n=1214), unemployed (n=413). The data obtained on the occupation and cardiovascular risk factors: smoking, alcohol consumption, obesity, cholesterol level, lipoproteids, glucose, anamnesis of cardiovascular diseases and real presence of arterial hypertension, ischemic heart disease (IHD) by Minnesota criteria, and angina pectoris by Rose score. In statistical processing, with the aim to relieve age differences of the groups we standardized by the age via direct method, and in regression analysis there was a parameter "age".Results. In employed men there was statistically significant lower prevalence of smoking — among workers 40,2%, unemployed 52,6% (p=0,011). CHD in anamnesis in 5,4% and 11,9%, resp. (p=0,0047), arterial hypertension — 47,9% and 57,1%, resp. (p=0,043), angina by Rose score — 5,3% and 13,6%, resp. (p=0,00001), CHD by Minnesota code — 5,0% and 9,2%, resp. (p=0,048), CHD by 3 epidemiological criteria — 9,4% and 20,4%, resp. (p=0,00020). In women employment was related to lower prevalence of smoking — 15,4% among workers, 22,4% — unemployed (p=0,038) and CHD by Minnesota code —5,4% and 9,6%, resp. (p=0,019). Occupational status for men leads to the decrease of arterial pressure by 3,4 mmHg in average (p=0,051), increase of total cholesterol concentration by 0,231 mmol/L (p=0,041), and in women — increase of HDL by 0,135 mmol/L (p=0,0024).Conclusion. Better cardiovascular health do have employed people comparing to unemployed: tendency is stronger in men. The results reflect common tendency of the higher level of health among employed young inhabitants comparing to unemployed.